ANALGESIC AND ANTI-INFLAMMATORY ACTIVITY OF VARIOUS EXTRACTS OF CLAUSENA DENTATA (WILLD.) ROEM - Kamaraj, Raju; Maduram, Annamalai (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: The present study was undertaken to study the analgesic and anti-inflammatory activity of various extracts of Clausena dentata. Clausena (Rutaceae) is a genus of about 23 species of unarmed trees and shrubs. The stem bark of C. dentata is used in veterinary medicine for the treatment of wounds and sprains. Even though C. dentata has a lot of potential medical uses, the study of pharmacological properties is very scarce. Methods: The plant C. dentata was collected in May 1999 from Kadagaman, near Tiruvannamalai, Tamil Nadu, India, and authenticated by Centre for Advanced Study in Botany, University of Madras, Chennai. The dry powder of stem bark was extracted with hexane, chloroform, and methanol. The extracts were subjected to thin-layer chromatography and phytochemical screening. Further, the extracts were tested for analgesic by the tail flick and anti-inflammatory by carrageenan-induced rat paw edema using plethysmometer. Results: Qualitative chemical tests revealed the presence of various phytochemicals such as alkaloids, glycosides, carbohydrate, proteins and amino acids, phytosterols, and volatile oil. The hexane, chloroform, and methanol extracts exhibited significant analgesic activity as compared to control group (Tween 80, 1%). The anti-inflammatory activity of C. dentata extracts revealed that the percent inhibition of carrageenan-induced rat hind paw edema was highly significant as compared to control group after 4 h of injection. Conclusion: The presence of coumarin and alkaloids all the extracts promising properties of analgesic and anti-inflammatory.